The internal logic of combining marxism with China's reality - Dong, Tingting (Національний технічний університет "Харківський політехнічний інститут", 2025)
To deepen the understanding of the combination of Marxism and China's reality, it is necessary to thoroughly analyze its internal logic. The logical relationship between the three dimensions of theoretical logic, practical logic, and value logic in system analysis has important theoretical significance and practical value for promoting the sinicization and modernization of Marxism.
Keywords: sinicization of marxism; theoretical logic; practical logic; value logic